Optimalisasi Kinerja Karyawan melalui Penguatan Disiplin dan Kualitas Lingkungan Kerja: Peran Strategis Motivasi Kerja sebagai Variabel Intervening - Rinawati Zailani; Dewi Anjani Febriani; Sulistiono Sulistiono (Jurnal Riset Akuntansi, 2026)
The success of an organization depends heavily on the individual performance of its members, so the organization will continue to strive to improve the productivity and professionalism of its human resources. This study aims to examine the effects of work discipline and work environment on employee performance, with work motivation serving as a mediating variable. A quantitative research approach was employed, involving 50 employees as respondents. Data were collected using a structured questionnaire based on a Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) through SmartPLS 3.0. The findings reveal that work discipline has a positive and significant effect on work motivation and employee performance. The work environment has a positive but insignificant effect on work motivation, while it has a positive and significant effect on employee performance. Furthermore, work motivation positively and significantly influences employee performance. The mediation analysis indicates that work motivation significantly mediates the relationship between work discipline and employee. This suggests that employees with higher levels of discipline tend to be more motivated, which subsequently enhances their performance. In contrast, work motivation does not significantly mediate the relationship between the work environment and employee performance, indicating that improvements in the work environment may affect performance more directly than through motivational mechanisms. In conclusion, employee performance can be enhanced through stronger work discipline, a supportive work environment, and increased work motivation. Among these factors, work discipline plays the most important role in improving both employee motivation and performance.